Factors Relating to Smoking Behaviour in Akap Bus Driver in Bekasi City Terminal in 2021 - Hanny Afny; Devi Angeliana Kusmaningtiar; Susi Shoryasari; Ade Heryana (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2021)
Abstract Background:Smoking behavior is an activity or activity of burning cigarettes and then sucking it and exhaling it and can cause smoke. Based on the results of Riskesdas 2018, 62,9% of men and 4.8% of women aged 15 years and over used tobacco (Riskesdas, 2018). Based on the results of a preliminary study conducted on 15 AKAP bus drivers, 10 bus drivers have smoking behavior and 5 other people do not have smoking behavior.Objectives:The purpose of this study was to determine the factors related to smoking behavior in AKAP bus drivers in Bekasi Citu Terminal.Research Metodes: This type of research is a cross sectional design research. The sample in this study was the AKAP bus driver at the Bekasi City Terminal as many as 115 respondents with the sampling technique of purposive sampling. Analysis of the data used is the chi square test. Findings: Univariate results showed the highest proportion of smoking behavior was 76.5%. The results of the chi square test showed that there was no relationship between knowledge (PR = 1.197; 95% CI = 0.975 – 1.470), attitude (PR = 1.206; 95% CI = 0.990 – 1.471), peer influence (PR = 1.201; 95% CI = 0.981 – 1.469), and the effect of advertising (PR = 1.091; 95% CI = 0.887 – 1.341) on AKAP bus drivers at Bekasi City Terminal in 2021.Conclusion: With the large number of smoking behavior among AKAP bus drivers, it is hoped that there will be a policy from Bekasi City Terminal to hold Non-Smoking Area. Keywords: Smoking behavior; cigarettes; AKAP bus driver